The adequacy of remedies in consumer transactions: special study in the motor vehicle repair and service industry in Malaysia - Amin, Naemah; Abu Bakar, Elistina (Malaysian Consumer and Family Economics Association (MACFEA), 2012)
It has been understood that consumers consume not only of products, but also of services. Motor vehicle repair and service is a common and regular service used by consumers in Malaysia. As such, this paper analyses the extent to which the laws of Malaysia provides adequate remedies to consumers when they have problems with garages. The discussion includes the analysis on the contract law as well as the statutory provisions under the Malaysian Consumer Protection Act 1999 (CPA). A small survey has also been carried out to point out the most favorable remedies sought by Malaysian consumers. A total of 400 respondents participated in the study through stratified random sampling and the respondents were requested to state the remedies that they desired if they pursue legal action. It is very explicit from the result that majority ofthe respondents (75.8%) desire the same garage to solve their problems or to rectifY their mistake rather than going to other garages. Only 26.8% wants money as compensation. This finding provides evidence that the demand ofconsumers are not in line with the remedies provided under the contract laws where do not provide for the remedy of specific performance or remedy of repairing the defect unless in limited circumstances. Nevertheless, the CPA has introduced the redress of remedying the defect which brings the law in line with reality by giving a consumer, in many cases. the remedy that he/she really wants.